Prevalence of hypothyroidism amongst pregnant women: a study done in rural set up - Pillai, Nancy S.; Bennet, Jemela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Thyroid disorders are the commonest endocrine disorders affecting women of reproductive age group. The most frequent thyroid disorder in pregnancy is maternal hypothyroidism. During early pregnancy the foetus is totally dependent on maternal thyroid hormone supply. Thyroid hormone is critical for foetal brain and intellectual development and some preventable conditions like abruption, pre-eclampsia etc. which produce morbidity and pose special risk for pregnancy and the developing foetus. Methods: All subjects enrolled in the study as per the inclusion criteria will be subjected to a detailed history and clinical examination using a predesigned proforma. A serum TSH value will be sent in 1st trimester between 6-10 weeks period of gestation for all pregnant women. Results: The prevalence of thyroid dysfunction in pregnancy was 10.8% with hypothyroidism being 9.2%, out of which 8.5% were cases of subclinical hypothyroidism and 0.7% were cases of overt hypothyroidism. On assessing the risk factors for developing thyroid dysfunction in pregnancy, increases in incidence were seen with maternal age and increasing BMI, both of which were statistically significant. Conclusions: This study showed an increased prevalence of hypothyroidism in pregnancy recommending a need for universal screening for all pregnant women in the first trimester itself. This study aims at validating the efficacy of the above-mentioned screening.